The early diversification of ray‐finned fishes (Actinopterygii): hypotheses, challenges and future prospects. (3rd October 2022) - Henderson, Struan; Dunne, Emma M.; Fasey, Sophie A.; Giles, Sam
ABSTRACT: Actinopterygii makes up half of living vertebrate diversity, and study of fossil members during their Palaeozoic rise to dominance has a long history of descriptive work. Although research interest into Palaeozoic actinopterygians has increased in recent years, broader patterns of diversity and diversity dynamics remain critically understudied. Past studies have investigated macroevolutionary trends in Palaeozoic actinopterygians in a piecemeal fashion, variably using existing compendia of vertebrates or literature‐based searches. Here, we present a comprehensive occurrence‐based dataset of actinopterygians spanning the whole of the Palaeozoic. We use this to produce the first through‐Palaeozoic trends in genus and species counts for Actinopterygii. Diversity through time generally tracks metrics for sampling, while major taxonomic problems pervading the Palaeozoic actinopterygian record obscure diversity trends. Many described species are concentrated in several particularly problematic 'waste‐basket' genera, hiding considerable morphological and taxonomic diversity. This taxonomic confusion also feeds into a limited understanding of phylogenetic relationships. A heavy sampling bias towards Europe and North America exists in both occurrence databases and available phylogenetic matrices, with other regions underrepresented despite yielding important data. Scrutiny of the extent to which spatial biases influence the actinopterygian record is lacking, as is research on other forms of bias. Low richness in some time periods may be linked to geological biases, while the effects of taphonomic biases on Palaeozoic actinopterygians have not yet been investigated. Efforts are already underway both to redescribe poorly defined taxa and to describe taxa from underrepresented regions, helping to address taxonomic issues and accuracy of occurrence data. New methods of sampling standardisation utilising up‐to‐date occurrence databases will be critical in teasing apart biological changes in diversity and those resulting from bias. Lastly, continued phylogenetic work will enable the use of phylogenetic comparative methods to elucidate the origins of actinopterygian biogeography and subsequent patterns of radiation throughout their rise to dominate aquatic faunas.